Parental Knowledge of Cigarette Smoke Exposure in Children with Acute Respiratory Infection: The Role of Education and Occupation in Yogyakarta - Deni Lusiana; Riris Anggita Putri; Dina Apriliyanti (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2026)
Background: Acute Respiratory Infection (ARI) affects both the upper and lower respiratory tracts. Parents with less knowledge about cigarette smoke have a negative impact on family members, especially toddlers, which can trigger the incidence of Acute Respiratory Infection in children. This study aims to analyze the relationship between education and employment levels and the level of parental knowledge about the dangers of cigarette smoke in toddlers aged 0-5 years with Acute Respiratory Infection at Yogyakarta Hospital. Methods: This study employs a quantitative descriptive cross-sectional design. The sampling technique was accidental sampling with 35 respondents. In analyzing the data, this study used Spearman's rank correlation test. Results: The test showed a significant relationship between parents' education level and their knowledge of ARI in children, indicated by a p-value of 0.010 (<0.05). In contrast, there was no significant relationship between parents' occupational status and their knowledge of ARI in children, with a p-value of 0.266 (>0.05). While education level is associated with knowledge, parental occupation is not. These findings suggest that factors beyond education and work may also influence parents' knowledge. The data also indicates that most parents are aware of the dangers of cigarette smoke; however, family members who smoke may contribute to the risk of ARI in children. Conclusion: Higher educational attainment is strongly associated with increased knowledge about the dangers of cigarette smoke, particularly in the context of preventing ARI in children and managing ARI cases.